PENGARUH RASIO KEUANGAN DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DENGAN VARIABEL BELANJA MODAL SEBAGAI VARIABEL MODERASI PADA PEMERINTAHAN PROVINSI TAHUN 2015-2019 - Slamet Widodo (Pusat Kajian Anggaran, 2021)
Regional governments role becomes dominant in determining the implementation of regional development in increasing economic growth. Gross Regional Domestic Bruto (GRDP) is illustrated by several ratios that measure regional finances, namely the degree of decentralization (X1), regional financial dependence (X2), the degree of Regional Owned-Enterprises contribution (X3), the effectiveness of Local Origin Revenues (X4), and the allocation of regional capital expenditures (X5). This study discusses the effect of these financial ratios on GRDP with the capital expenditure variable as a moderating variable in the Provincial Governmentin the 2015-2019 period. The data used is the accumulated Provincial Regional State Budget and GRDP data for the period 2015-2019. The methodology used is the fixed effect panel data regression model and regression analysis with moderated regression analysis (MRA). The purpose of this study is to formulate regional financial management policies that are more effective in increasingregional economic growth. Result shows that the model is Fixed Effect and variables X1, X2, and X4 significantly affected GRDP, while variables X5 and X4 otherwise. The results of the MRA analysis show that the moderating variable of capital expenditure has a significant influence on the relationship between the regional financial dependence variable and the GRDP.